TRENDS OF EVOLUTION OF REPRODUCTIVE MEDICINE IN EUROPE - Veljko Vlaisavljević (Zdravniški Vestnik, 2018)
Demographic changes in European countries are quite similar in average. In times when the population number is globally increasing, most European countries are facing a negative trend. Interestingly, the termination of unwanted pregnancies also follows the same trend. In some European countries, where negative demographic trends are regulated by means of the immigration policy, only the number of children born with artificial insemination is constantly increasing. In developed countries the share of children conceived in such a manner presents an important demographic shift in the number of newborn children. Although there are not many demographic studies available, it appears that the problem of infertility is getting more and more addressed in national health policies. Recent advances in education and certification of the knowledge and institutions dealing with reproductive medicine was demonstrated by the European Society for Reproductive Medicine and Emb- riology (ESHRE) who support development of this part of gynecology. Significant support to the increased needs for infertility treatment was recognized in the resolution of European Parlament related to Demographic future of Europe.